Alternative splicing misregulation secondary to skeletal muscle regeneration - Orengo, James P. (2011)
OBJECTIVE: Misregulation of alternative splicing has become a molecular hallmark of myotonic dystrophy type 1 (DM1) in which neonatal splice variants are expressed in adult skeletal muscle. Splicing misregulation is induced by RNA containing expanded CUG repeats expressed from the expanded mutant allele by sequestration of Muscleblind-like 1 (MBNL1) protein within nuclear RNA foci and increased CUGBP, Elav-like family member 1 (CELF1) protein levels. Misregulated splicing has also been identified in other neuromuscular disorders suggesting either that diseases with different molecular causes share a common pathogenic mechanism or that misregulated splicing can also be a common secondary consequence of muscle degeneration and regeneration. METHODS: In this study we examined regulation of alternative splicing in four different mouse models of muscular dystrophy including DM1, limb-girdle muscular dystrophy, congenital merosin-deficient muscular dystrophy, Duchenne muscular dystrophy, and two myotoxin (cardiotoxin and notexin) muscle injury models. RESULTS: We show that DM1-like alternative splicing misregulation and altered expression of MBNL1 and CELF1 occurs in non-DM1 mouse models of muscular dystrophy and muscle injury, most likely due to recapitulation of neonatal splicing patterns in regenerating fibers. In contrast, CELF1 was elevated in nuclei of mature myofibers of the DM1 model consistent with a primary effect of pathogenic RNA expression. INTERPRETATION: Splicing misregulation in DM1 is a primary effect of RNA containing expanded CUG repeats. However, we conclude that splicing changes can also be observed secondary to muscle regeneration and this possibility must be taken into account when evaluating cause-effect relationships between misregulated splicing and disease processes.